E -Module Based on Multi-Representation Topics of Inventors Who Changed the World in Class VI Elementary School - Kurniasari, Dita; Susanti, Rahmi; Siahaan, Sardianto Markos; Raharjo, Makmum (Universitas Sebelas Maret, 2024)
This research aims to develop multi-representation- based e-modules in thematic learning in elementary schools. The problem currently occurring is that students have difficulty understanding the material because the teaching materials used are still textbooks. Therefore, it is necessary to develop interesting teaching materials in the form of e-modules. The type of research used is development research using the Ronwtree development model combined with Tessmer evaluation which consists of planning, development and evaluation stages. The population in this study was 30 class VI students. The methods used in collecting data in this research were observation, interviews, questionnaires and tests. Validity test results at the expert stage review shows that the assessment from language experts got an average score of 94% in the very valid category, while from material experts the total percentage was 88% in the very valid category, and media experts got a total score of 96% in the very valid category. So the average score of the three experts is 9.2 % in the very valid category. The E-Module practicality test results from the small group were 82.1% in the very practical category. The multi-representation based e-Module was declared effective on student learning outcomes. This can be seen from the N-gain results, namely 0.6 with medium criteria. So it can be concluded that the E-Module based on multiple representations of the topic of inventors who changed the world in class VI SDN 146 Palembang is declared valid, very practical and effective on student learning outcomes.